Internalization of Qur’anic Values in Islamic Religious Education Learning: A Qur’anic Pedagogical Perspective - Muhammad Zein; Agustian Ramadhona (Newinera Publisher, 2026)
This study explores the integration of Qur’anic values within Islamic Religious Education (IRE) by employing a Qur’anic pedagogical lens that emphasizes holistic character formation, spiritual awareness, and transformative learning. The research addresses the central question of how Qur’anic principles can be systematically internalized in classroom practices to enhance students’ ethical, cognitive, and affective development. Using a qualitative descriptive approach supported by textual analysis of Qur’anic verses, curriculum documents, and classroom observations, the study maps pedagogical strategies that align instructional processes with Qur’anic educational ideals. The findings reveal that internalization occurs effectively through three interconnected dimensions: value-oriented learning design, dialogical and reflective teaching methods, and teacher modeling grounded in prophetic pedagogy. These dimensions foster deep moral consciousness, strengthen students’ spiritual identity, and encourage ethical decision-making in daily life. The study concludes that Qur’anic pedagogy offers a robust framework for cultivating meaningful learning experiences in IRE, requiring educators to integrate scriptural values not merely as cognitive content but as lived practices embedded in pedagogical interactions.